PV-Battery System Design for an Indigenous People School in Malaysia - Basir Khan M.R.; Al-Fattah J.; Pasupuleti J.; Tahmasebi M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Carbon dioxide; Digital storage; Electric batteries; Hybrid systems; Rural areas; Sensitivity analysis; Battery storage system; Data collection; Hybrid configurations; Hybrid optimization; Indigenous people; Net present cost; Renewable energy fractions; System configurations; Economic analysis